Management of Curriculum and integrative learning of Islamic religious education and vocational school at SMKN 3 Malang, Indonesia - Wiyono, Dwi Fitri; Hakim, Dian Muhammad; Hassan, Abd. Rauf (Technium Social Sciences Journal, 2023)
This paper discusses the new formulation of a curriculum and learning management system in Islamic religious education and an integrative-vocational collaborative model by combining learning materials and objectives through a measurable curriculum planning and management system in accordance with the vocational school curriculum and Islamic values. This research produces an integrative curriculum and learning model by combining one scientific discipline (vocational) and Islamic education disciplines, the researcher gives the term “Nested Integrated Model”: integration of proficiency targets achieved on certain topics in vocational material with targets achieved in Islamic religious education.